THE ORIGINS AND DEVELOPMENT OF TRANSITIONAL JUSTICE STUDIES - STRUPINSKIENĖ, LINA (Politologija, 2012)
Induced by the worldwide wave of democratization, transitional justice studies emerged in the late 1980s and early 1990s as a new field of study in democratization. Since then, they have experienced rapid developments and evolved into an independent multi-disciplinary inquiry covering aspects of international relations, comparative politics, political theory, sociology, and even philosophy.This article aims to present and critically evaluate the state of the art in the field of transitional justice studies as well as to address several problematic issues. First, what factors have been shaping the current research trends in the field? Second, what are the major theoretical and methodological problems faced by transitional justice scholars? And finally, what kind of data and research are missing and what information could contribute to the further development of the field? The driving force behind this article is the notion that academic self-reflection is useful for both scholars interested in transitional justice processes and practitioners who are implementing various transitional justice policies nationally and internationally.The article focuses mainly on the literature written by political scientists. The analysis also covers several key publications by sociologists, legal scholars, and human rights advocates. Reflections from practitioners have been considered due to their growing agenda-setting abilities for the implementation of transitional justice instruments.The article begins with a discussion of the transitional justice concept, which is followed by a brief overview of the developments of the study field. It notes that the classical works on transitional justice focus on the implementation of various transitional justice policies, their adaptability to specific needs of societies, emerging after a repressive rule or a violent ethnic conflict, and the possible benefits resulting from an active engagement in the past, whereas the more recent inquiries demonstrate an important empirical turn. Since the year 2000, there has been an increase in comparative studies attempting to empirically verify the effect of transitional justice mechanisms on societal transitions. This new wave of research calls into question the previous assumption regarding the ability of transitional justice mechanisms to contribute to peace and reconciliation and demonstrates that this relationship may be more complicated than initially thought.The article continues with the discussion of the main debates in the field. It covers the well-known debates on Peace vs. Justice, Truth vs. Justice, and provides an overview of the problems faced by those attempting to explore the causal relationship among the transitional justice mechanisms and societal reconciliation, democratization and peace. The methodological issues of definitions and problems with proving causality are addressed. The article concludes with recommendations for future inquiries.